Participatory Communication of Returned Indonesian Migrant Workers in Green Economy Entrepreneurship: A Bibliometric Study - Nani Nurani Muksin; Oktaviana Purnamasari; Jumail (Ikatan Sarjana Komunikasi Indonesia, 2025)
This article examines the strategic role of participatory communication, post-return entrepreneurship of Indonesian migrant workers, and the green economy framework in promoting sustainable development initiatives. Grounded in theories of participatory communication and green entrepreneurship, the study applies a bibliometric approach to scientific publications from 2000 to 2024, sourced from the Dimensions database and mapped using VOSviewer. The analysis identifies research trends, author networks, and dominant keywords, revealing that the integration of participatory communication, post-migration entrepreneurship, and green economy remains limited and underexplored. It also highlights weak institutional connectivity among Indonesian academic communities, with minimal positioning of returned migrant workers as active agents of sustainable transformation. The findings suggest that participatory communication can significantly strengthen community engagement, enhance program ownership, and drive social change. Consequently, the study recommends adopting transformative and collaborative approaches in development communication to empower returned migrant workers in advancing local green economies. These insights contribute to achieving the Sustainable Development Goals (SDGs), particularly SDG 8 (decent work), SDG 10 (reduced inequalities), and SDG 13 (climate action), by integrating migration into inclusive development strategies.